5 Ways to Market Your Practice - Khan, Mohammad (Canadian Journal of Optometry, 2023)
You’ve worked hard for your practice, and it’s time to share your hard work to the public. Building a patient base is a journey, but implementing different marketing strategies can be the kickstart you need to begin building up your practice in the marketing world. Your patients need to know what’s going on at your practice, whether you have new services or products that need to be upfront and center of all your marketing efforts. Here are 5 ways to market your practice.